Prevalence and risk factors of toxigenic Clostridioides difficile asymptomatic carriage in 11 French hospitals - Jolivet, Sarah; Couturier, Jeanne; Grohs, Patrick; Vilfaillot, Aurélie; Zahar, Jean-Ralph; Frange, Pierre; Casetta, Anne; Moulin, Véronique; Lawrence, Christine; Baune, Patricia; Bourgeois, Cléo; Bouffier, Axel; et al. (Frontiers in Medicine, 2023)
Clostridioides difficile infection (CDI) incidence has increased over the last 20 years. Studies suggest that asymptomatic carriers may be an important reservoir of C. difficile in healthcare settings. We conducted a point prevalence study to estimate the toxigenic C. difficile asymptomatic carriage rate and the associated risk factors in patients >3 years old. Between September 16, 2019 and January 15, 2020, all patients hospitalized in 11 healthcare facilities in the Paris urban area were included in the study. They were screened on the day of the survey for toxigenic C. difficile carriage by rectal swab and interviewed. Isolates were characterized by PCR ribotyping and multiplex PCR targeting toxin genes. A logistic regression model was used to determine the risk factors associated with toxigenic C. difficile asymptomatic carriage using uni- and multivariate analysis in the subpopulation of patients >3 years old. During the study period, 2,389 patients were included and screened. The median age was 62 years (interquartile range 35–78 years) and 1,153 were male (48.3%). Nineteen patients had a previous CDI (0.9%). Overall, 185/2389 patients were positive for C. difficile (7.7%), including 93 toxigenic strains (3.9%): 77 (82.8%) were asymptomatic (prevalence 3.2%) whereas 12 (12.9%) were diarrheic. Prevalences of toxigenic C. difficile were 3.5% in patients >3 years old and 7.0% in ≤3 years old subjects, respectively. Toxigenic strains mainly belonged to PCR ribotypes 106 (n = 14, 15.0%), 014 (n = 12, 12.9%), and 020 (n = 10, 10.8%). Among toxigenic strains, 6 (6.4%) produced the binary toxin. In multivariate analysis, two factors were positively associated with toxigenic C. difficile asymptomatic carriage in patients >3 years old: multidrug-resistant organisms co-carriage [adjusted Odd Ratio (aOR) 2.3, CI 95% 1.2–4.7, p = 0.02] and previous CDI (aOR 5.8, CI 95% 1.2–28.6, p = 0.03). Conversely, consumption of raw milk products were associated with reduced risk of toxigenic C. difficile colonization (aOR 0.5, CI 95% 0.2–0.9, p = 0.01). We showed that there was a low prevalence of asymptomatic toxigenic C. difficile carriage in hospitalized patients. Consumption of raw milk prevents toxigenic C. difficile colonization, probably due to the barrier effect of milk-associated bacteria.